Intensity modulated radiation therapy (IMRT) with simultaneously integrated boost shortens treatment time and Is noninferior to conventional radiation therapy followed by sequential boost in adjuvant breast cancer treatment: results of a large randomized phase III trial (IMRT-MC2 trial) - Hörner-Rieber, Juliane; Forster, Tobias; Hommertgen, Adriane; Häfner, Matthias; Arians, Nathalie; König, Laila; Harrabi, Semi B.; Schlampp, Ingmar; Weykamp, Fabian; Lischalk, Jonathan W; Heinrich, Vanessa; Weidner, Nicola; et al. (International journal of radiation oncology, biology, physics, 2021)
In the modern era, improvements in radiation therapy techniques have paved the way for simultaneous integrated boost irradiation in adjuvant breast radiation therapy after breast conservation surgery. Nevertheless, randomized trials supporting the noninferiority of this treatment to historical standards of care approach are lacking.
Available online 13 December 2020
Gesehen am 23.04.2021